2015
DOI: 10.1140/epje/i2015-15077-4
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability of a horizontal phase boundary subjected to shear motion

Abstract: Abstract. We investigate the stability of slowly smearing phase boundary that appears at the contact of two miscible liquids. A hydrodynamic flow is imposed along the boundary. The aim is to find out whether the slow diffusive smearing of a boundary can be overrun by faster mixing. The phase-field approach is used to model the evolution of the binary mixture. The linear stability in respect to 2D perturbations is studied. If the heavier liquid lies above the lighter liquid, the interface is unconditionally uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
7
3
0
Order By: Relevance
“…The increase of the Cahn number increases the surface tension effect, which makes the interface less prone to deformations, and this reduces the amplitude of the waves and the amplitude of the hydrodynamic motion in the layer. Similar observations were earlier achieved with the help of the linear stability analysis [26].…”
Section: Numerical Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The increase of the Cahn number increases the surface tension effect, which makes the interface less prone to deformations, and this reduces the amplitude of the waves and the amplitude of the hydrodynamic motion in the layer. Similar observations were earlier achieved with the help of the linear stability analysis [26].…”
Section: Numerical Resultssupporting
confidence: 88%
“…Stronger viscous and diffusion effects should result in a closure of the zone of the Holmboe instability, although such cases are not modelled in the present work. Similar stability diagrams were earlier reported by other researchers [11,12,26]. In particular, figure 6a is adopted from our earlier work [26], where this diagram is obtained by using the linear stability analysis for an interface that separates two semiinfinite domains of two miscible liquids.…”
Section: Numerical Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…These results, including appearance of the cloudy regions near the droplet's ends, are is in agreement with the experimental pictures [22]. Figure 2 depicts the results of the numerical simulations of the droplet's time evolution obtained for the 4 In [37,38], the influence of the interface thickness on the stability of a phase boundary has been studied. It has been found that if the interface thickness is smaller than the thickness that corresponds to the thermodynamic equilibrium value δ 0 (21), then the thickness of the transition zone quickly adjusts to the thermodynamic equilibrium value, i.e.…”
Section: Numerical Resultssupporting
confidence: 82%